Javanology’s Communication Strategies: Empowering, Adapting, and Developing Javanese Culture through Intercultural Communication and Dialogue - Muhammad Taufiq Al Makmun (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
This article is an ethnographic report based on the observation conducted in Javanology Center of Excellence for Javanese Tradition of Sebelas Maret University in Indonesia. This intends to report the communication strategies done by the center in order to win public acceptance and supports as an organization which focuses on the development of local indigenous Javanese culture amongst the modern developed Javanese society and global culture. Based on the types of activities observed by the writer, the center uses four communication strategies against the attribution toward Javanese culture, they are: (1) self empowerment through academic movement, (2) adapting to the modern cultural practices and technology, (3) developing training center and networks targeting younger generation globally, and (4) employing intercultural communication to bridge the conflict through dialogues.